Soil solarization for the control of damping-off of different vegetable crops in the nursery - and N.K. SHARMA, HARENDER RAJ, M.L. BHARDWAJ (Indian Phytopathology, 2002)
Soil solarization with transparent polyethylene mulch (25 éŽš) controlled damping off pathogens of different vegetable crops in the nursery. Nursery-bed soil was flood irrigated and then covered with transparent polyethylene sheet for 40 days. Mulching with polyethylene resulted in 13.5é³¦ higher temp. at 8 cm soil depth with an average maximum temp. of 49.7? Soil solarization for 40 days killed the Pythium spp. and Fusarium spp. up to 30 cm soil depth. A nursery of 10 different vegetable crops raised later in solarized beds recorded 18.3 to 42.0% higher seed germination, lower incidence of post-emergence damping off and had better seedling vigour.